Effect of prerestorative short-term clear aligner therapy in restorative treatment planning - KORKUT, BORA (My University, 2023)
Statement of problem. One of the major challenges in restorative dentistry is to provide optimal esthetics in a minimally invasive way. The optimization of dental esthetics and function is directly related to the position and alignment of the anterior teeth, but whether prerestorative clear aligner therapy will enhance esthetics and minimize restorative needs is unclear. Purpose. The purpose of this clinical study was to evaluate the effect of prerestorative maxillary and mandibular second premolar to second premolar clear aligner therapy in minimizing the need for restorative treatment. Material and methods. Fifty adult patients treated with clear aligners (Invisalign Go; Align Technology) were included in this study. Previously generated 3-dimensional orthodontic simulations and clinical photographs in the ClinCheck/6.0 software program were used. Three restorative treatment plans for each participant were generated for initial (no aligners), Express (after using 7 aligners), and Lite Packages (after using 20 aligners) by 2 blinded restorative dentistry instructors. The maxillary and mandibular teeth in the smile-line (to the second premolars) were included. Assessment criteria were the estimated number of restorations, restoration surfaces and preparations and incisal edge inclusion, and the need for gingival leveling. The Friedman test and Cochran Q test were used for statistical analyses (a=.05). Results. A strong positive correlation was found between the 2 instructors (P<.001). Estimated number of restorations (10 [3 to 16]a ) decreased significantly for Express (6 [0 to 14]b ) and Lite Packages (4 [0 to 8]c ) (P<.001). The estimated number of restoration surfaces (28.5 [9 to 48]a ) decreased significantly for Express (15 [0 to 42]b ) and Lite Packages (9.5 [0 to 24]c ) (P<.001). While the estimated number of teeth to be prepared for recontouring (7 [0 to 16]a ) was significantly less for Express (3 [0 to 10]b ) and Lite Packages (0 [0 to 4]c ) (P<.001), the incisal edge inclusion (10 [3 to 16]a ) was significantly less for Express (6 [0 to 14]b ) and Lite Packages (4 [0 to 8]c ) (P<.001). The need for gingival leveling (26 [52%]a ) decreased significantly for Express (20 [40%]a ) and Lite Packages (7 [14%]b ) (P<.001). Conclusions. Prerestorative short-term clear aligner therapy might conserve tooth structure and reduce the number of restorations. The application of the Invisalign Lite Package was more effective than the Invisalign Express Package for second premolar to second premolar alignment. (J Prosthet Dent 2023;-:---)
Keywords: Diş Hekimliği; Klinik Bilimler; Sağlık Bilimleri; Dentistry; Clinical Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry